Development of the Crisis and Emergency Intervention Skills Scale (CEISS) and an analysis of its psychometric properties - F. A. Muñoz; R. Alarcón; J. Trillo; J. Miranda; C. Polo (Scientific Reports)
Abstract Emergency psychology is a branch of psychology that, although it began several years ago due to dramatic events around the world, is increasingly being established in the day-to-day work of the emergency department. Due to the very specific nature of this type of intervention, it is essential that, in addition to proper training and experience, emergency psychologists have a series of competencies. In this study, we developed a questionnaire, the Crisis and Emergency Intervention Skills Scale (CEISS), ad hoc for this research, and we determined the relationship of the CEISS score with the most relevant competencies. These capacities to intervene and provide assistance in crisis situations were found to be the sum of several skills. Positive correlations of CEISS scores with resilience, attention, clarity and regulation, which are related to emotional intelligence, were found. Knowing what psychological competencies are necessary for the correct performance of this type of task, as well as for professionals to have good psychological self-protection, is of great help when managing situations that require this type of intervention.